Is it possible to terminate resuscitation in accordance with the termination of resuscitation rule? - Kashiura, Masahiro; study group, SOS-KANTO 2012 (Journal of Thoracic Disease, 2016)
We appreciate the interests of Bernhard et al. and Yoon et al. regarding our article in Critical Care, which showed a high false-positive rate (FPR) for the termination of resuscitation (TOR) rules in patients with out-of-hospital cardiac arrest (OHCA) with a non-cardiac etiology (1). We agree with their views (2,3), and herein we respond to their comments and provide results of our reanalysis.